Global trends in flipped classroom research within mathematics education over past two decade: A bibliometric analysis - Kadarisma, Gida; Juandi, Dadang; Darhim, Darhim (Jurnal Infinity, 2024)
This research aims to provide a bibliometric review of trends in using flipped classrooms in mathematics learning research. This research is essential to analyze the extent of the flipped classroom research trend in mathematics learning as a reference for future research in this research.  Bibliometric analysis was used to analyze and classify bibliographic data by considering inclusion and exclusion criteria. The database used was Scopus using the Bibliometrix application. The search was carried out using the keywords "flipped classroom", "mathematics learning", and "K-12". The results revealed a total of 102 articles related to the keywords. The data showed increased publications over the last two decades, with 2023 being the year with the highest publication count. Apart from that, Indonesia had the highest rate of producing related articles. The most relevant author was Hew Khe Foon. The most cited article was "A self-regulated flipped classroom approach to improving students' learning performance in a mathematics course". The Indonesian Education University was the most productive affiliate related to this theme. Furthermore, the journal "Educational Technology and Society" was found to be the most prolific journal for publishing research outcomes. New themes emerged in flipped classroom research, such as conceptual and procedural knowledge. Future researchers are expected to utilize the research focus to determine the theme to be explored. It is recommended that further researchers incorporate the novelty discussed in this research.